SLACK RESOURCES, RAPAT DEWAN KOMISARIS DAN FEMINISME DEWAN DIREKSI TERHADAP KUALITAS PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Iswatin Lutfi Hasanah; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThe resarch was conducted to find out how the influence of Slack Resources, Board of Commissioners Meetings and Board of Directors Feminism on the Quality of Corporate Social Responsibility Disclosure. The population used in this study is a consumer goods manufacturing sector manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2015-2018. The selection of sample using Purposive Sampling and multiple linear regression analysis methods. The results of this study are slack resources anf feminism the board of directors has a positive effect on the quality of corporate sosial responsibility disclosure. Whereas the board of commissioners’ meeting did not affect the quality of corporate sosial responsibility disclosure.Keywords: slack Resources, Board of Commissioners Meeting, CSR, Feminist Ethical Theory, Disclosure Quality